ANALYSIS OF FACTORS AFFECTING PUBLIC POVERTY IN BULUKUMBA DISTRICT - Rosdiana Rosdiana; Inanna Inanna; Agus Syam; Muhammad Hasan; Thamrin Tahir (HUMAN: South Asian Journal of Social Studies, 2021)
This study aims to analyze the effect of GRDP, unemployment and education on poverty in the Bulukumba district. This study used quantitative methods, while data collection was carried out by means of documentation on documents obtained at the Central Bureau of Statistics, Bulukumba regency regarding GRDP, Unemployment and Education for the period 2012-2019. The results of this study indicate that: (1) Based on the results of partial testing, GRDP, education and unemployment each have a positive and significant effect in realizing poverty in the people of Bulukumba district. (2) PDRB, Education and Unemployment have a simultaneous influence in realizing the poverty of the people of Bulukumba Regency